A Systematic Review of Teacher-Delivered Behavior-Specific Praise on K–12 Student Performance. (April 2019) - Royer, David J.; Lane, Kathleen Lynne; Dunlap, Kristin D.; Ennis, Robin Parks
Behavior-specific praise (BSP) is a core component of many positive behavioral interventions and supports at each level of prevention, often used to increase student academic outcomes and/or reduce inappropriate behavior. We conducted a systematic literature review to explore this low-intensity, teacher-delivered strategy, applying Council for Exceptional Children (CEC) quality indicators and standards to determine whether BSP can be considered an evidence-based practice (EBP). Included articles ( N = 6) investigated BSP delivered by a classroom teacher in K–12 traditional school-based settings with academic and/or behavioral student outcome measures. Findings indicated using BSP increased student time on task, decreased inappropriate behaviors, and reduced student tardiness. All studies met our 80% weighted coding criterion. We concluded BSP can be categorized as a potentially EBP based on CEC guidelines. Limitations and directions for future inquiry are presented.